Influence of Cereals on the Production Performance and Biochemical Profile of Broiler Chickens - Saber Beghoul, Katiba Beroual, Med Cherif Abdeldjelil (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: This experiment was conducted to determine the effects of the incorporation of these two cereals on the zootechnical performances, the biochemical profile, the characteristics of the carcass and the consumable offal of chickens. Methods: 318 broiler chicks (day-old) were divided into 3 lots. In group "barley", maize was partially replaced by crushed barley during the three conventional rearing phases, they are 31%, 32% and 35% respectively. In "triticale group" ; the chickens here consumed a feed in which maize was partially substituted during the three phases, they are 31% at starting, 32% during growth and 35% during finishing, respectively. Results: The best weight growth was obtained in the group fed the "barley" ration, followed by the "triticale" ration. The lowest live weight was recorded with the "control. On the other hand, the results show that triticale supplementation in the diet does not change the carcass characteristics of the chickens: non-significant variation between the "control" and "triticale" groups (P>0.05). Conclusion: Barley proved to have a positive influence on production performance such as live weight and carcass yield when incorporated into the ration.